Redistributive forces of the Irish tax-benefit system - O'Donoghue, Cathal (Statistical and Social Inquiry Society of Ireland, 2003)
This paper charts the main changes in structure of the Irish system of tax and social benefits over the period 1955-2002. It analyses the evolution of the redistributive forces in the system over the period and considers the effect of the incremental reform on the complexity of policy and resulting impact on incentives.
Read before the Society, 28 November 2002
Keywords: Social assistance; Replacement rate; Welfare state; Tax-benefit system; 314.15